SISTEM PENYARADAN PADA EKSPLOITASI HUTAN PINUS DI JAWA TENGAH - S Sutopo; Maman M Idris (Jurnal Penelitian Hasil Hutan, 1985)
A paper  mill  is to  be erected  in Cilacap, Central Java in the near future. The raw material  must  come  from  the hilly pine  forests  in  the  Pekalongan  and Banyumas  area. The  mill's daily intake ranges between 1,000-1,500 m3 of  relatively small  diameter  pine  logs. Therefore manual yarding  system  must  be improved  to increase its productivity. One way to do this is to yard  with a  wheeled  cariage.The purpose of this investigation  is to  determine the feasibility of  this yarding system in hilly pine forest terrain. The investigation reveals the following   :Yarding system by  Roda II is favourable  in  the  hilly pine  forest area in Central Java.This system increases  the  income  per  manday  approximately  by 31%  compared to the  traditional system (ngglebeg) for a  distance of  1,0 km,  and  18%  for a distance of  2.0 km.Yarding productivity by Roda II is approximately  1.58  m3 per day.